Comparison of the kinematics of the full-instep and pass kicks in soccer - Levanon, J.; Dapena, J. (Medicine & Science in Sports & Exercise, 1998)
The goal of this study was to gain a better understanding of the mechanics of the inside-of-the-foot passing shot used in soccer ("pass kick"). Result: To impact the ball with the medial aspect of the foot in the pass kick, the player orients the pelvis, the right leg, and the foot more toward the right and introduces a medial component of foot velocity. However, most of the speed of the foot is still generated through knee extension.